Prevention of Bone Metastases - Joerger, Markus; Gnant, Michael; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
Bone metastases continue to be a major cause of morbidity in cancer patients, but improved understanding of the biology of bone metastases has led to the identification of drugs that are of potential value in not only their treatment but also their prevention. This book, written by recognized experts in the field, provides a detailed overview of current knowledge on this subject. One important focus of the book is the efficacy of bisphosphonates in preventing bone metastases in patients with breast, lung, and prostate cancer and disease progression in cases of multiple myeloma.  The combined use of bisphosphonates and cytostatics is also discussed, with a report on first clinical data.  Further topics addressed include the significance of the bone microenvironment, special issues in the elderly patient, the use of bone turnover markers, and initial findings obtained with denosumab.
Keywords: Oncology .; Surgical oncology; Oncology; Surgical Oncology